Kepuasan Konsumen Berdasar pada Kualitas Pelayanan dan Kualitas Produk : Survei pada Konsumen Lazatto Chicken & Burger Kawalu - Sinta Durmawati, (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine simultaneously and partially consumer satisfaction based on service quality and product quality of Lazatto Chicken & Burger Kawalu. The method used in this research is a quantitative approach with a survey method. The population in this study amounted to 100 respondents. The type of data used in this study is primary data obtained through a questionnaire. The analysis used is the classical assumption test and multiple regression analysis using SPSS version 26. The results show that service quality and product quality simultaneously have a significant effect on customer satisfaction at Lazatto Chicken & Burger Kawalu, partially service quality has a significant effect on consumer satisfaction, while Product quality has a significant effect on Consumer Satisfaction Lazatto Chicken & Burger Kawalu.